Optimización de los procesos de rendimiento en la eficiencia productiva de la industria agraria - Aguilar Mauricio, Maria (2024)
This project focuses on developing a mathematical model to optimize efficiency in agricultural production, with special attention to small farmers in Villa Santa Sofía, Peru. The main objective is to maximize production with limited resources, such as land, water and capital, while maintaining a sustainable balance with the environment. A linear regression mathematical model is implemented with the purpose of not only increasing agricultural productivity, but also preserving natural resources and mitigating negative environmental impacts associated with agriculture. The fractional fertilization strategy throughout the rice growth cycle highlights the effective implementation of fertilizer use. Farmers have demonstrated the importance of nourishing plants at key times to optimize their growth, development and grain production. However, the need to adjust these recommendations according to the particularities of the soil, climate and local agricultural practices is emphasized. Likewise, the essentiality of pesticides in crop protection is highlighted to guarantee food security, increase productivity and contribute to agricultural sustainability.